Computer network security : fourth International Conference on Mathematical Methods, Models, and Architectures for Computer Network Security, MMM-ACNS 2007 St. Petersburg, Russia, September 13-15, 2007 : proceedings - MMM-ACNS; Gorodetski, Vladimir I.; Kotenko, Igor; Skormin, Victor A. (Communications in Computer and Information Science, 2007)
This book constitutes the refereed proceedings of the Fourth International Conference on Mathematical Methods, Models, and Architectures for Computer Network Security, MMM-ACNS 2007, held in St. Petersburg, Russia in September 2007. Its objective was to bring together leading researchers from academia and governmental organizations as well as practitioners in the area of computer networks and information security.